Bilateral differences in knee and ankle loading of the support limb during maximal instep soccer kicking - Sinclair, J.; Hobbs, S. J. (Science & Sports, 2016)
Objective: Kicking actions have been implicated in the aetiology of soccer injuries and the unilateral nature of kicking may influence this. The biomechanics of the support limb are distinct between the dominant and non-dominant during instep kicking, although little is known about how these alterations in mechanics may be associated with the risk of injury. This study aimed to examine vertical ground reaction forces as well as knee/ankle loads when performing maximal kicks with the dominant and non-dominant limbs. Material and methods: Twenty male academy soccer players performed maximal kicks with their dominant and non-dominant limbs striking a force platform with their support limb. Vertical ground reaction forces and knee/ankle joint kinetics were obtained from each limb and then contrasted using paired t-tests. Results: Significant increases in knee extensor and abduction moment were found when using the non-dominant limb. It was also shown that patellofemoral contact force was significantly higher in the non-dominant kicking condition. Conclusions: The findings from the current investigation have clinical significance and support the notion that kicking with the non-dominant limb may be associated with and increased injury aetiology.